2005
DOI: 10.1007/s11010-005-2540-3
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of myocardial infarct size by doxycycline: A role for plasmin inhibition

Abstract: Myocardial ischemia-reperfusion (I/R) is associated with the activation of matrix metalloproteinases (MMPs) and serine proteases. We hypothesized that activation of MMPs and the serine protease plasmin contribute to early cardiac myocyte death following I/R and that broad-spectrum protease inhibition with doxycycline (DOX) preserves myocyte viability. Rats treated daily with or without DOX beginning 48 h prior to experimentation were subjected to 30 min of coronary occlusion and 2 days of reperfusion. DOX pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 42 publications
0
41
0
1
Order By: Relevance
“…A deficiency of, as well as up-regulation of, PLG and F2 beyond physiological levels can lead to multiple pathological outcomes, including thrombosis caused by partial or inadequate degradation of blood clots, defective wound healing, and excessive bleeding (55)(56)(57). Plasmin is postulated to influence the progression of cardiovascular diseases through activation of collagenases and matrix metalloproteinases and resultant degradation of matrix proteins (58) and has also been implicated in metabolic syndrome (59). PLG, F2, and their receptors are also closely linked to regulation of cardiovascular inflammatory responses and have been suggested by others to influence cell migration through regulation of growth factor and chemokine pathways and acute phase response signaling through activation of C3 component of complement system (60).…”
Section: Discussionmentioning
confidence: 99%
“…A deficiency of, as well as up-regulation of, PLG and F2 beyond physiological levels can lead to multiple pathological outcomes, including thrombosis caused by partial or inadequate degradation of blood clots, defective wound healing, and excessive bleeding (55)(56)(57). Plasmin is postulated to influence the progression of cardiovascular diseases through activation of collagenases and matrix metalloproteinases and resultant degradation of matrix proteins (58) and has also been implicated in metabolic syndrome (59). PLG, F2, and their receptors are also closely linked to regulation of cardiovascular inflammatory responses and have been suggested by others to influence cell migration through regulation of growth factor and chemokine pathways and acute phase response signaling through activation of C3 component of complement system (60).…”
Section: Discussionmentioning
confidence: 99%
“…MMPs are known to contribute to the development of various heart defects, including CH and myocardial infarction, and DOX, an FDA-approved drug with a known absorption/ toxicity profile, has been shown to inhibit MMPs (Golub et al, 1998;Grenier et al, 2002;Griffin et al, 2005). This prompted us to test the drug in two different mouse models of CH.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to several other candidates, doxycycline (DOX) was predicted as a potential therapy for pathological CH. The software identified DOX as a potential therapeutic partly because it was previously shown to generally inhibit MMPs (Griffin et al, 2005), which suggested to us that it might reduce a hypertrophic phenotype. DOX is a very well tolerated antibiotic and is also FDA approved, making it a particularly attractive candidate for CH therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the rat model of MI, a robust and early increase in myocardial levels for the gelatinases MMP-2 and MMP-9 have been reported (138,334,425,442). Using an MMP-2/-9 specific fluorogenic substrate, Villarreal et al (469) demonstrated significant myocardial proteolytic activity as early as 2 h following coronary ligation (469).…”
Section: Animal Modelsmentioning
confidence: 99%